Motor learning and control concepts and applications - Magill, Richard A.; Anderson, David 1965 December 21- (McGraw-Hill Education, 2017)
Motor Learning and Control: Concepts and Applications provides an introductory study of motor learning and control for students who aspire to become practitioners in exercise science, physical education, and other movement-oriented professions. The text opens with an introduction to motor skills and control, continues through attention, memory, and learning, and ends with a discussion of instruction, feedback, and practice methods. The text's strong research base, clear presentation and practical applications will help students build a solid foundation in motor skills and prepare them for further exploration on their own.